Design, Synthesis and In Vitro Biological Activity of Novel C-7 Methylene Congeners of Furanoallocolchicinoids - Iuliia A. Gracheva; Elena V. Svirshchevskaya; Ekaterina S. Shchegravina; Yulia B. Malysheva; Alsu R. Sitdikova; Alexey Yu. Fedorov (MDPI AG, 2023)
A series of novel heterocyclic colchicine derivatives bearing a C-7 methylene fragment were synthesized via Wittig, Horner-Wadsworth-Emmons and Nenajdenko-Shastin olefination approaches. The in vitro biological activities of the most promising compounds were investigated using MTT assays and cell cycle analyses. Compounds with an electron withdrawing group on the methylene fragment exhibited substantial antiproliferative activity towards COLO-357, BxPC-3, HaCaT, PANC-1 and A549 cell lines. The spatial orientation of the substituent at the double bond significantly influenced its biological activity.